Multimedia Information Virality Versus Privacy Protection: An Ethical Study of News Visualization in Multimedia Journalism - Ali, Afifah; Muhammad Anshar Akil (International Journal of Islamic Studies, 2026)
This study aims to analyze the dilemma between the phenomenon of information virality and the protection of individual privacy within the ethics of news visualization in multimedia journalism in the new media era. Employing a qualitative approach through the Systematic Literature Review (SLR) method, secondary data were collected from books, scholarly journals, academic articles, and relevant journalistic ethical regulations published within the last five years. The findings reveal that the characteristics of digital media and social media platform algorithms have contributed to the increasing culture of information virality through the utilization of emotional elements (emotion) and narratives (stories) within the STEPPS framework. In practice, media orientation toward speed and engagement often leads to privacy violations, such as the publication of photographs or videos of accident victims, individuals experiencing traumatic situations, and the identities of minors without proper censorship or consent. This unethical visual exploitation has negative psychological and social impacts, including trauma, cyberbullying, stigmatization, and reputational damage caused by permanent digital footprints. Based on the Social Responsibility Theory of the Press, press freedom in fulfilling the public interest must be balanced with respect for human dignity and individual privacy rights. Therefore, this study emphasizes the importance of implementing ethical measures through visual identity protection (censorship/blurring), mandatory content verification, enforcement of the Journalistic Code of Ethics, and prioritizing the protection of vulnerable groups in order to establish healthy and responsible multimedia journalism within the digital environment.